Lissajous curves with a finite sum of prime number frequencies - Barna, Imre Ferenc; Mátyás, László (Annals of Mathematics and Physics, 2022)
The Ulam spiral inspired us to calculate and present Lissajous curves where the orthogonally added functions are a finite sum of sinus and cosines functions with consecutive prime number frequencies.